2013
DOI: 10.1016/j.physletb.2013.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Holographic thermalization in Gauss–Bonnet gravity

Abstract: In the spirit of AdS/CFT correspondence, we study the thermalization of a dual conformal field theory to Gauss-Bonnet gravity by modeling a thin-shell of dust that interpolates between a pure AdS and a Gauss-Bonnet AdS black brane. The renormalized geodesic length and minimal area surface, which in the dual conformal field theory correspond to twopoint correlation function and expectation value of Wilson loop, are investigated respectively as thermalization probes. The result shows that as the Gauss-Bonnet coe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 53 publications
2
42
0
4
Order By: Relevance
“…3 In addition, for both the thermalization probes, we observe an overlapped region where the noncommutative parameter has few influence on them for a fixed boundary separation. In fact, this phenomenon has also been observed in modified gravity [35,36]. It is explained that this effect arises from the difference of the temperature of the dual conformal field for the thermalization only becomes fully apparent at distances of the order of the thermal screening length l D ∼ (π T ) −1 , where T is the temperature of the dual conformal field.…”
Section: Discussionmentioning
confidence: 66%
“…3 In addition, for both the thermalization probes, we observe an overlapped region where the noncommutative parameter has few influence on them for a fixed boundary separation. In fact, this phenomenon has also been observed in modified gravity [35,36]. It is explained that this effect arises from the difference of the temperature of the dual conformal field for the thermalization only becomes fully apparent at distances of the order of the thermal screening length l D ∼ (π T ) −1 , where T is the temperature of the dual conformal field.…”
Section: Discussionmentioning
confidence: 66%
“…We study holographic entanglement entropy in a dynamical (Vaydia type) scenario in Gauss-Bonnet gravity where the collapse of a null shell results in the formation of an asymptotically AdS black hole. Previous studies of HEE in this background have been focused on thermalization time of the field theory [10][11][12].…”
Section: Jhep09(2017)127mentioning
confidence: 99%
“…We will take the region γ to be a spherical cap on the boundary delimited by θ ≤ θ 0 . 8 Then based on the definition of area and (2.2), (3.8) can be rewritten as We will also employ Maxwell's equal area law to locate the first order phase transition temperature, namely T a in (b) 10) in which T (δS) is an interpolating function obtained from the numeric result, and δS min , δS max are the smallest and largest roots of the unstable regions, which satisfy the equation T (δS) = T x . Surely the values of the phase transition temperature T x depends on the choice of Q and b.…”
Section: Phase Structure Probed By Holographic Entanglement Entropymentioning
confidence: 99%
“…To probe these fascinating phenomena in field theory, one should employ some non-local observables such as equal time two point correlation function for a scalar operator, Wilson loop, and holographic entanglement entropy, which are dual to the geodesic length, minimal area, and minimal volume individually in the saddle point approximation. It has been shown that these observables can probe the nonequilibrium thermalization behavior [4][5][6][7][8][9][10][11][12][13][14][15], superconducting phase transition [16][17][18][19][20][21][22][23], and cosmological singularity [24,25].…”
Section: Introductionmentioning
confidence: 99%